Quo vadis, biological treatment for psoriasis and psoriatic arthritis? - Olszewska, Barbara; Adamski, Zygmunt; Czarnecka-Operacz, Magdalena (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2018)
Psoriasis is a chronic autoimmune disease that affects approximately 2–3% of the world’s population. Although the cutaneous manifestations of the disease are the most prevalent, psoriasis is also associated with a systemic inflammation and various co-morbidities linked with autoinflammatory processes. One of those processes is psoriatic arthritis, an inflammatory, seronegative spondyloarthropathy that develops in 13.8–30% of psoriatic patients at some point of their lives. Over the past 15 years the therapeutic options for severe and generalized psoriasis have broadened immensely with the introduction of biological agents to everyday practice. We present a quick overview of current biological therapies in the treatment of psoriasis and prospects for forthcoming advancements in biological treatment.